2017
DOI: 10.1016/j.devcel.2017.10.011
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1-Mediated Inhibition of 4EBP1 Is Essential for Hedgehog Signaling-Driven Translation and Medulloblastoma

Abstract: Mechanistic target of rapamycin (MTOR) cooperates with Hedgehog (HH) signaling, but the underlying mechanisms are incompletely understood. Here we provide genetic, biochemical, and pharmacologic evidence that MTOR complex 1 (mTORC1)-dependent translation is a prerequisite for HH signaling. The genetic loss of mTORC1 function inhibited HH signaling-driven growth of the cerebellum and medulloblastoma. Inhibiting translation or mTORC1 blocked HH signaling. Depleting 4EBP1, an mTORC1 target that inhibits translati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 75 publications
4
56
0
Order By: Relevance
“…This includes mechanistic target of rapamycin(mTOR) signaling, a metabolic pathway that has been shown to crosstalk with the IDO1 pathway in medulloblastoma 48 . mTOR promotes medulloblastoma tumor progression 49,50 and targeting mTOR may be a promising strategy to treat medulloblastoma 51 . Studies characterizing the molecular mechanisms and subgroup-specficity of 1-L-[ 18 F]FETrp uptake in medulloblastoma are currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…This includes mechanistic target of rapamycin(mTOR) signaling, a metabolic pathway that has been shown to crosstalk with the IDO1 pathway in medulloblastoma 48 . mTOR promotes medulloblastoma tumor progression 49,50 and targeting mTOR may be a promising strategy to treat medulloblastoma 51 . Studies characterizing the molecular mechanisms and subgroup-specficity of 1-L-[ 18 F]FETrp uptake in medulloblastoma are currently in progress.…”
Section: Discussionmentioning
confidence: 99%
“…4EBP1 is a downstream protein of mTOR, which inhibits eIF4E (the subunit of eIF4F). When 4EBP1 is in a low phosphorylation state, it inhibits the translation of mRNA by binding tightly with eIF4E while reducing interaction with cap-binding protein eIF4G to form the initial complex of eIF4F [32]. It is known that eIF4F controls the expression of many proteins that are associated with cell proliferation, expansion, and apoptosis, such as Mcl-1 (antiapoptotic molecule), cyclin D1 and D3 (cell-cycle regulators), and C-Myc (oncoprotein) [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It was found that canonical Hh signaling required mTORC1-mediated inhibition of 4E-BP1, since the mTOR inhibitor Torin1 suppressed GLI1 mRNA induction in response to SAG, and KD of 4E-BP1 , by shRNAs, reversed the effect of Torin1 on GLI1 mRNA expression. Inhibition of mTORC1 further suppressed Hh-dependent growth of cerebellar and medulloblastoma [ 95 ]. It is interesting to note that Torin1 but not rapamycin could suppress SAG-mediated Hh signaling.…”
Section: Mechanisms Leading To Hh/mtor Crosstalkmentioning
confidence: 99%